P695 Feasibility and safety of strictureplasties performed by laparoscopic approach for complicated Crohn's disease: A prospective observational cohort study. (25th January 2019) - Sampietro, G M; Colombo, F; Frontali, A; Baldi, C; Conti, L; Dilillo, D; Fiorina, P; Maconi, G; Ardizzone, S; Corsi, F; Zuccotti, G; Foschi, D
Abstract: Background: Laparoscopy (LP) is considered the gold standard for the surgical treatment of complicated Crohn's disease (CD). Conventional and non-conventional strictureplasties (SP) are indicated as a valid alternative to resection for fibrotic strictures, but such a complex and often multiple suturing has been considered until now the prerogative of open surgery. Since no data are available in the literature, aims of the present study is to assess feasibility and safety of SP performed by laparoscopic approach. Methods: Data of all the patients undergoing surgery for CD were entered into our prospective database (ProSaDS-CD). A prospective protocol for laparoscopic approach was started in 2007. We compared patients treated by LP and by open approach (OP) in terms of preoperative patients' characteristics; number, site, and type of diseased segments; surgical procedure; perioperative complications and long-term results. All the consecutive, unselected patients with at least one small bowel location of CD at primary surgery were included. Pure colonic or recurrent disease were exclusion criteria. Clavien–Dindo classification was used for postoperative complications. Follow-up was performed at 3, 6 and 12 months after surgery, and then every year or in case of necessity. Results: Between January 1995 and January 2018, 1166 patients entered the ProSaDS-CD. 557 met the inclusion criteria. LP and OP groups consisted of 297 and 260 patients, respectively. Overall conversion rate was 5.3%. Postoperative recovery was faster, and duration of surgery and hospital stay shorter in VL group ( p < 0.05). Morbidity (Clavien–Dindo III or IV) and mortality rates were 4.3% and 0, 3% in VL group and 4.2% and 0.7% in OP group (ns). No differences were present in terms of patients' history and clinical characteristics. In VL group 653 segments were involved (min 1 – max 25), and 290 bowel resections (52.3%), 146 conventional SP (26.4%), and 118 non-conventional SP (21.3%) were performed. In OP group were performed 228 bowel resections (46.4%), 143 conventional SP (29%), and 121 non-conventional SP (24.6%), for a total of 468 locations (min 1 – max 21) (ns). The mean length of diseased bowel, resection, and bowel sparing were 30.5 ± 26.2 cm, 23.6 ± 17.5 cm, and 23.3% (VL); and 24.5 ± 20, 3 cm, 19.3 ± 14.5 cm, and 20.8% (OP) (ns). Mean follow-up was 6.3 ± 3.2 years. Conclusions: This is the first study comparing the use of SP in open and laparoscopic surgery. No differences were found in term of safety and efficacy, number and type of SP, and bowel sparing. VL group had faster recovery and shorter duration of surgery and hospital stay.